Climate Change in Sub-Saharan Africa Fragile States : Evidence from Panel Estimations - Maino, Rodolfo (IMF Working Papers; Working Paper ;, 2022)
Fragile states in sub-Saharan Africa (SSA) face challenges to respond to the effects of climate shocks and rising temperatures. Fragility is linked to structural weaknesses, government failure, and lack of institutional basic functions. Against this setup, climate change could add to risks. A panel fixed effects model (1980 to 2019) found that the effect of a 1 degree C rise in temperature decreases income per capita growth in fragile states in SSA by 1.8 percentage points. Panel quantile regression models that account for unobserved individual heterogeneity and distributional heterogeneity, corroborate that the effects of higher temperature on income per capita growth are negative while the impact of income per capita growth on carbon emissions growth is heterogeneous, indicating that higher income per capita growth could help reduce carbon emissions growth for high-emitter countries. These findings tend to support the hypothesis behind the Environmental Kuznets Curve and the energy consumption growth literature, which postulates that as income increases, emissions increase pari passu until a threshold level of income where emissions start to decline.